THE EFFECT OF TAX AVOIDANCE, LEVERAGE, AND PROFITABILITY ON COST OF DEBT IN MANUFACTURING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Louis Louis; Yenni Yenni (Proceeding of International Conference on Entrepreneurship (IConEnt), 2022)
For a company's operational activities to run smoothly, it requires funds to finance the company's activities as working capital, one of the ways is through debt financing. This financing option would result in interest payment, hence resulting in the cost of debt. This research aims to study the effect of tax avoidance, leverage, and profitability on cost of debt in manufacturing companies listed on Indonesia Stock Exchange (IDX). This study is a quantitative descriptive study that applies the purposive sampling method, with 78 manufacturing companies listed on the IDX from 2017 to 2019 were chosen as the sample of this study. To analyze the data obtained, this study used a multiple linear regression model. This study found that tax avoidance has no effect on the cost of debt in manufacturing companies listed on the IDX. Meanwhile, leverage and profitability both have positive significant partial effect on the cost of debt in manufacturing companies listed on the IDX. Furthermore, tax avoidance, leverage, and profitability have significant simultaneous effect on cost of debt in manufacturing companies listed on IDX. Collectively, these variables have 19.1% effect on cost of debt, while the remaining 80.9% effect is caused by factors that are not addressed in this study, such as good corporate governance, inflation, sales growth, and payback period.